(untitled) (Research, Society and Development, 2023)
Objective: The purpose of this study was to review the literature on the impact of the COVID-19 pandemic on the quality of sleep of healthcare professionals. Methods: Searches were performed using the following databases for data collection: PubMed, Scielo and Lilacs. Results: The sample for this review consisted of 5 studies, which covered the quality of sleep of healthcare professionals during the COVID-19 pandemic. Conclusions: The study pointed out the harmful effects of the COVID-19 pandemic on the quality of sleep of healthcare professionals, which include poor sleep, insomnia, bruxism and difficulty falling asleep, in addition to psychological and mental disorders such as anxiety, stress and depression.